AN EXPERIMENTAL INVESTIGATION OF MIRROR LIGHTING - Erbil, Filiz Acari; Ozturk, Leyla Dokuzer (ZNACK PUBLISHING HOUSE, 2016)
The aim of this study is to investigate the preferred vertical illuminance and luminaire placements for mirror lighting experimentally. For this purpose, a mirror is fixed on a wall of the mock-up room and three linear luminaires are placed around the mirror; one on each side and one above the mirror. Twenty-seven lighting scenarios have been designed by using three luminaires around the mirror for local lighting and four indirect suspended luminaires providing general lighting in the room. Lighting scenarios were based on different lighting arrangements and six vertical illuminance steps between 300 lx and 2000 lx. Surveys have been performed to determine the impressions and judgements of the participants in terms of illuminance provided, shadows produced and glare caused in each scenario. Findings obtained by means of the survey have been evaluated and guiding criteria for mirror lighting design are introduced.
Keywords: mirror lighting; vertical illuminance; glare; shadow; Engineering; Optics